(untitled) (International relations and international law Journal, 2016)
In article objective signs of structure of a criminal offense, action or inaction and its public and dangerous consequences are exposed social legal to the analysis. Need of studying of the question posed is that at establishment of a criminal and legal ban to this or that act the legislation has to consider a measure of intensity of socially dangerous act which at the correct assessment would provide justice and stability of norms of criminal law and differentiation of administrative offense from a criminal offense. According to the author, the sociological analysis of criminal and legal problems shouldn’t will extend on sanity and age of the person who made socially dangerous act. As the reason of it serves that fact that not only the criminal law, but also all branches of the right provide behavior and responsibility of the responsible person capable to bear legal responsibility.